Connectopathy in Autism Spectrum Disorders: A Review of Evidence from Visual Evoked Potentials and Diffusion Magnetic Resonance Imaging - Yamasaki, Takao; Maekawa, Toshihiko; Fujita, Takako; Tobimatsu, Shozo (Frontiers in Neuroscience, 2017)
Individuals with autism spectrum disorder (ASD) show superior performance in processing fine detail, but often exhibit impairments of gestalt face and global motion perception and visual attention, in addition to core social deficits. Increasing evidence suggests that social deficits in ASD may arise from abnormal functional and structural connectivity between and within the distributed cortical networks that are recruited during social information processing. Because the human visual system is characterized by a set of parallel, hierarchical multistage network systems, we hypothesized that altered connectivity of visual networks may contribute to social cognition impairment in ASD. In this review, we focused on studies of altered connectivity of visual and attention networks in ASD using visual evoked potentials (VEPs), event-related potentials (ERPs) and diffusion tensor imaging (DTI). A series of VEP, ERP and DTI studies conducted in our lab have demonstrated complex alterations (the impairment and enhancement) of visual and attention networks in ASD. Thus, recent data suggest that the atypical visual perception observed in ASD is caused by altered connectivity within the parallel visual pathways and attention networks, contributing to the impaired social communication observed in ASD. Therefore, we conclude that the underlying pathophysiological mechanism of ASD constitutes a “connectopathy”.